Caracterización geoquímica y petrografía de los cuerpos intrusivos básicos, aflorantes en la región de cáceres y puerto romero, departamentos de cundinamarca y boyacá, colombia (2000)
In the Caceres-Puerto Romero area, crop out some basic intrusive bodies shaped like sills and dikes, which are intruding the cretaceous sedimentary rocks of La Paja and Simití formations. In a broad outline, they show "pseudostratification" and a regional trench of N 10-20oE, as remarkable features.  The geochemical characterisation carrying through for the analysed samples, shows SiO2 concentrations between 50 and 57 %, belonging to the subalcaline series with sodic tendency and tholeiitic character; geochemically they are gabbros, granodiorites and diorites. Regarding to the petrography, they are composed mostly of intermediate to calcic plagioclase, piroxenes (augite, diopside and hypersthene) and quartz. Amongst the prevailing textures found in these rocks are ophitic, subophitic and granular. For geochemical characterization and for tectonic environment discrimination were used diagrams developed originally for effusive rocks by differents authors. In accordance with the results obtained in this work, it is possible to state that the origin of the basic intrusive bodies took place at the distensive within plate setting, as a consequence of the formation of an intracontinental rift at the Berriasian -Coniacian ages. In this period the sizeable thinning of the continental crust gave rise to a set of very deep faults along which began the rising of the magma as a result of partial melt of the mantle.